Patient participation in multidisciplinary tumor conferences: How is it implemented? What is the patients' role? What are patients' experiences?. (17th August 2021) - Ansmann, Lena; Heuser, Christian; Diekmann, Annika; Schellenberger, Barbara; Biehl, Claudia; Danaei, Mahmoud; Eichler, Christian; Heinz, Dina; Hocke, Andrea; Malter, Wolfram; Melekian, Badrig; Metin, Havva; et al.
Abstract: Background: Prior research has shown that around 5%–7% of patients in breast cancer centers in Germany participate in the discussion of their own case within a multidisciplinary tumor conference (MTC). The PINTU study is one of the first to research this practice. The objective is to describe (a) how patient participation in MTCs is implemented, (b) what is the role of patients, and (c) how patients experience MTCs. Methods: MTCs in six breast and gynecological cancer centers in North Rhine‐Westphalia, Germany, with and without patient participation, are studied prospectively by (non)participatory, structured observation. Breast and gynecological cancer patients completed surveys before, directly after, and 4 weeks after MTC participation. Data are analyzed descriptively. Results: Case discussions of a sample of n = 317 patients (n = 95 with MTC participation and n = 222 without) were observed. Survey data were obtained from n = 242 patients (n = 87 and n = 155). Observational data showed heterogeneity in the ways MTC participation was practiced. Among participating patients, 89% had the opportunity to express their opinion and 61% were involved in decision‐making. Whereas most patients reported positive experiences and would recommend participation, some had negative experiences and regretted participating. Conclusions: Due to a lack of recommendations, hospitals implement patient participation in MTCs in many different ways. So far, it is unknown which setting and procedures of MTC participation are beneficial for patients. However, existing evidence on communication in cancer care together with this exploratory study's findings can build the basis for developing recommendations for hospitals that invite their patients to MTCs. Clinical trial registration number: German Clinical Trials Register Nr. DRKS00012552. Abstract : Patient participation in multidisciplinary tumor conferences is a seldom, but constant reality in breast cancer care and the way it is currently practiced shows large variation. Whereas most patients reported positive experiences and would recommend participation, some had negative experiences and regretted participating. Practice recommendations for hospitals that invite their patients to tumor conferences need to be developed.